2015
DOI: 10.1167/iovs.15-16609
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Corneal Subbasal Whorl-like Nerve Plexus: More Accurate Depiction of the Extent of Corneal Nerve Damage in Patients With Diabetes

Abstract: Our findings indicated that IVCM measurements of the whorl-like patterns may accurately define the extent of corneal nerve damage in order to monitor diabetic peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…30 Interestingly, the whorl density wCNFL did not vary with presence or duration of diabetes or HbA1c, but was largely preserved. In three recent studies that did not employ widefield mosaicking or depth correction techniques, [31][32][33] reduced CNFL in the whorl region was reported in diabetes-a finding that could not be confirmed in our cohort. In another study, mosaic images indicated a decline in whorl density in diabetes, although the study was limited to only two subjects.…”
Section: Discussioncontrasting
confidence: 92%
“…30 Interestingly, the whorl density wCNFL did not vary with presence or duration of diabetes or HbA1c, but was largely preserved. In three recent studies that did not employ widefield mosaicking or depth correction techniques, [31][32][33] reduced CNFL in the whorl region was reported in diabetes-a finding that could not be confirmed in our cohort. In another study, mosaic images indicated a decline in whorl density in diabetes, although the study was limited to only two subjects.…”
Section: Discussioncontrasting
confidence: 92%
“…We found that the density of basal epithelial cells increased with age. Previous studies failed to find a significant correlation between basal epithelial cell density and age (Gambato et al 2015, Niederer et al Vanathi et al 2003), although there was a trend in a study by Niederer et al (2007) andVantahi et al (2003). However, according to our results, the association with age disappeared after the DM1 diagnosis was established, which may indicate the opposite influence of DM1 on epithelial cell density.…”
Section: Discussionmentioning
confidence: 87%
“…The diabetic patients were subdivided, based on a fundus examination (using biomicroscopy and fundus photography) and need of therapy intervention, into three groups: 1) without retinopathy, 2) mild retinopathy, and 3) severe retinopathy. Patients with no signs of retinopathy were included in the "no DR" group, patients with mild or moderate non-proliferative retinopathy (NPDR), according to the Early Treatment of Diabetic Retinopathy Study (ETDRS) (Wilkinson et al 2003, Utsunomiya et al 2015 were assigned to the "mild DR" group, and patients with severe NPDR or proliferative retinopathy (PDR) were placed in the "severe DR" group.…”
Section: Evaluation Of Retinal Statusmentioning
confidence: 99%
“…Accumulation of sorbitol and fructose leads to reduced nerve myoinositol, decreased sodium-potassium ATPase activity, 44 alteration in protein kinase C subunits, and slowed nerve CV in the peripheral nerves in diabetes. 45 It is likely that a similar mechanism occurs in the corneal nerves.…”
Section: Discussionmentioning
confidence: 99%